The unnoticed difference between antitrust and competition policy - Petra Luňáčková (Charles University in Prague, Institute of Economic Studies (IES), 2011)
This paper presents a model which focuses on differences between the competition policy of the EU and antitrust of the U.S. It introduces three versions - Neutral, American, and European. Two-stage game model takes the authority's perspective and describes options and behavior of antitrust officials when a firm engages in non-price vertical agreement (possibly restraint). Optimal behavior is expressed as expected income of the authority (EIA) which is a function of probability of wrong decision(s) in the course of action. It takes into account specific preferences, different types of errors, fear of those errors, and harm they might cause. Comparison shows some unnoticed features and results slightly in favor of the EU.
Keywords: L42; L44; C79; D79; 330; competition policy; antitrust; non-price vertical restraints; National Competition Authority; game form